O‘ZBEK XALQ MAQOLLARIDA OILA KONSEPTI VA UNING SEMANTIK XUSUSIYATI - Nasimova Shahnoza, (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article describes the concept of family and its semantic features in Uzbek folk proverbs. First, it was discussed in terms of cognitive linguistics. Then the term concept is explained and the differences between the concept and this lexeme are shown. During the writing of the article, the concept of family and its semantic features were highlighted on the basis of folk proverbs, and their synonymous possibilities were revealed. Descriptive method was also used during the research.